'Aur-Auran' as a Language of Digital Cultural Expression in Live Streaming: An Analysis of Its Connotation Meaning and Impact among Virtual Audiences - Chiquita Dewi Nada Nisrina; Kirana Aridhani Wahidah; Fatin Kusuma Anggraini; Elana Deswita; Aprilia; Lungit Kusuma Ningrum (English Lecturers and Teachers Association (ELTA), 2026)
This research aims to understand the connotative meaning in the lyrics of the song